ficacy of doxycycline and flumequine against experimentally induced colibacillosis in broiler chicks - Haji Akbar; Murad Khan; Ayaz Ali Khan; Muhammad Ali Khan; Shuaib1, Muhammad; Shamaila Fazal Akbar; Sobia Manzoor; Irshad-ur-rehman; Ahmad1 , Shakeel; Liaqat Ali; et al. (Advances in Aquaculture and Fisheries Management, 2019)
This study sought to determine comparative efficacy of doxycycline and flumequine for the treatment of Colibacillosis, which is an acute septicaemic disease caused by pathogenic Escherichia coli. This disease has illness coming on in the range widely, death rate is relatively high and some are up to more than 30%, have caused the enormous economic losses. The birds were infected intra-peritoneally with approx. 3 × 108 colony forming units per 0.25 ml of Enterotoxigenic E. coli (ETEC) and the infection developed within twelve hours. Chickens in group A1 were given doxycycline via the drinking water at a dose of 10 mg/kg body weight for 5 days, while group B1 was treated with flumequine at a dose of 12 mg/kg body weight for 5 days. The trial lasted for 9 days and then the surviving chickens were sacrificed. Doxycycline reduced the number of deaths and the severity of the clinical symptoms. In contrast, flumequine slightly influenced the mortality; however, it delayed death and reduced the severity of clinical symptoms. Present data indicate that doxycycline is highly effective for the treatment of experimental E. coli in chickens. The present study is of great importance for prescribing best effective drug against colibacillosis to avoid getting resistance to antibiotics.